Aluminizing for enhanced oxidation resistance of ductile refractory high-entropy alloys - Sheikh, Saad; Gan, Lu; Tsao, Te-Kang; Murakami, Hideyuki; Shafeie, Samrand; Guo, Sheng (Intermetallics, 2018)
Refractory high-entropy alloys (RHEAs) emerge as promising candidate materials for ultrahigh-temperature applications. One critical issue to solve for RHEAs is their balanced oxidation resistance and mechanical properties, mainly room-temperature ductility for the latter. Recently, it was found that existing ductile RHEAs are subject to catastrophic accelerated oxidation, also known as pesting. In this work, both alloying and surface coating, are applied to enhance the oxidation resistance of ductile RHEAs, with the focus on surface coating using the pack cementation method and more specifically, aluminizing. The oxidation resistance of two RHEAs, Hf0.5Nb0.5Ta0.5Ti1.5Zr, one recently identified ductile RHEA which pests in the temperature range of 600–1000 °C, and Al0.5Cr0.25Nb0.5Ta0.5Ti1.5, the newly designed ductile RHEA which does not pest but embrittles after oxidation, are studied after aluminizing at 900 °C using three different pack components. Aluminizing, if using the appropriate pack cementation parameters, can avoid pesting in Hf0.5Nb0.5Ta0.5Ti1.5Zr and alleviate the oxidation induced embrittlement in Al0.5Cr0.25Nb0.5Ta0.5Ti1.5, and holds the promise for further improving the RHEAs as potential ultrahigh-temperature materials. •Pack cementation using different pack compositions were experimented on two RHEAs.•Proper aluminizing can avoid pesting in the Hf0.5Nb0.5Ta0.5Ti1.5Zr RHEA.•Proper aluminizing can improve the embrittlement in Al0.5Cr0.25Nb0.5Ta0.5Ti1.5.•Aluminizing is promising to further improve RHEAs for high-temperature applications.